Pemanfaatan Limbah Sekam Padi sebagai Pupuk Organik - Duengo, Suleman; Musa, Weny J.A; Bialangi, Nurhayati; Kilo, Ahmad Kadir (Universitas Negeri Gorontalo, 2025)
This community service program addresses the challenge of limited access to affordable and eco-friendly fertilizers in Indonesia's agricultural sector. The program focuses on transforming rice husk waste into organic fertilizer, which can enhance soil fertility and reduce dependence on synthetic fertilizers. Rice husk, a byproduct of rice milling, contains essential nutrients like potassium, phosphorus, and calcium, making it an ideal raw material for organic fertilizer. The program took place in Desa Permata, Gorontalo, a village heavily reliant on maize farming but facing a shortage of high-quality organic fertilizers. Through a series of workshops, local farmers were trained in converting rice husk into organic fertilizers, thus empowering the community and fostering sustainable farming practices. The project demonstrated the economic and environmental benefits of utilizing agricultural waste, contributing to soil health and minimizing ecological impact. The results indicate that using rice husk-based fertilizers not only improves crop yields but also supports long-term environmental sustainability. This initiative serves as a model for other regions, highlighting the potential for circular economic practices in agriculture.